LEISURE HABITS IN HUNGARY AND ABROAD - Kinczel, Antonia (Acta Carolus Robertus, 2021)
In order for me to achieve the goals of my research, an online survey was compiled, as the difficulties and the constant changes in border closure-status did not give space for any other methods. Responds to my survey arrived both from Hungarian and Romanian young adults (N=323 of 18-25 year-olds). In my research, leisure habits, sports motivation, differences and similarities between the two countries were analysed, with the changes caused by Covid-19 as well, as I find it interesting to examine what changes have taken place in this epidemiological situation. Besides the basic statistics and frequency calculated, in order to examine correlations of the data Chi2 and paired t-test were used. Several of the hypotheses set up were considered true. The results show that young adults of Hungarian nationality living both in Hungary and outside of the border agree that sport plays an important role in a healthy lifestyle (average = 3.72, sd = 0.515). There is a difference however in the sports habits and sports motivation of those living in Hungary and of the Hungarians living outside of the border. In the case of the former, it became apparent, that they play sports and exercise more on a weekly basis (average = 4.437, sd = 2.8175) than those living in Romania (average = 3.678, sd = 2.4143) and are more satisfied with sports venues and opportunities. In terms of motivations, among domestic respondents, the love of sport and belonging to a community played a much prominent role. As Covid-19 reduced the number of sports events and opportunities (t = 4.026, p = 0.000), it is not surprising that the number of hours spent playing sports and exercising decreased as well (t = 4.598, p = 0.000). Moreover, there has been a noticeable change in sports venues as well as leisure activities. Most people already spend little time on sports and physical activities, which Covid-19 has only greatly decreased, so it became very important to make people aware of the many positive effects of sports and active leisure time spending, as well as to assess motivational factors and satisfaction levels, in order to live a healthier, more active, more balanced life.
Keywords: leisure time spending; Covid-19; motivation; sport